Evidentiary Strength of Land Ownership Certificates: An Analysis of Judicial Considerations in Supreme Court Decision Number 3762 K/Pdt/2022 - Ardiansyah, Aldi; Akbar, Muhammad Gary Gagarin; Abas, Muhamad (SIGn Jurnal Hukum, 2025)
The Land Ownership Certificate, as a manifestation of formal legal certainty, often clashes with substantive justice, particularly when its acquisition process is based on an unlawful act. This fundamental problem is central to Supreme Court Decision Number 3762 K/Pdt/2022. The decision contrasts a claim based on hereditary rights and physical possession with ownership based on a certificate originating from a juridically flawed transaction. This research aims to critically evaluate the appropriateness of the Supreme Court’s considerations in that decision. Using a normative juridical method enriched by critical discourse analysis and John Rawls’s theory of justice, this study deconstructs the paradigmatic dialectic between the judex factie and the judex juris. The analysis reveals that the decisions of the judex factie (District Court and High Court) tended to adopt a progressive approach by prioritizing material truth. In contrast, the Supreme Court applied a rigid legal positivism paradigm, protecting the certificate’s formal validity without conducting a substantial validity test of its acquisition process. It is concluded that while doctrinally justifiable, the Supreme Court’s decision is fundamentally unjust. It sacrifices the rights of the heir as the most vulnerable or least advantaged party and implicitly legitimizes the outcome of an illegality. This decision sets a dangerous precedent that reduces legal certainty to mere procedural formality and negates the law’s objective of achieving substantive justice in agrarian disputes.